Relationship of Mediterranean diet and caloric intake to phenoconversion in Huntington disease. - Marder, Karen; Gu, Yian; Eberly, Shirley; Tanner, Caroline M; Scarmeas, Nikolaos; Oakes, David; Shoulson, Ira (JAMA Neurol, 2013)
IMPORTANCE: Adherence to Mediterranean-type diet (MeDi) may delay onset of Alzheimer and Parkinson diseases. Whether adherence to MeDi affects time to phenoconversion in Huntington disease (HD), a highly penetrant, single-gene disorder, is unknown. OBJECTIVES: To determine if MeDi modifies the time to clinical onset of HD (phenoconversion) in premanifest carriers participating in Prospective Huntington at Risk Observational Study (PHAROS), and to examine the effects of body mass index and caloric intake on time to phenoconversion. DESIGN, SETTING, AND PARTICIPANTS: A prospective cohort study of 41 Huntington study group sites in the United States and Canada involving 1001 participants enrolled in PHAROS between July 1999 and January 2004 who were followed up every 9 months until 2010. A total of 211 participants aged 26 to 57 years had an expanded CAG repeat length (≥ 37). EXPOSURE: A semiquantitative food frequency questionnaire was administered 33 months after baseline. We calculated daily gram intake for dairy, meat, fruit, vegetables, legumes, cereals, fish, monounsaturated and saturated fatty acids, and alcohol and constructed MeDi scores (0-9); higher scores indicate higher adherence. Demographics, medical history, body mass index, and Unified Huntington's Disease Rating Scale (UHDRS) score were collected. MAIN OUTCOME AND MEASURE: Cox proportional hazards regression models to determine the association of MeDi and phenoconversion. RESULTS Age, sex, caloric intake, education status, and UHDRS motor scores did not differ among MeDi tertiles (0-3, 4-5, and 6-9). The highest body mass index was associated with the lowest adherence to MeDi. Thirty-one participants phenoconverted. In a model adjusted for age, CAG repeat length, and caloric intake, MeDi was not associated with phenoconversion (P for trend = 0.14 for tertile of MeDi, and P = .22 for continuous MeDi). When individual components of MeDi were analyzed, higher dairy consumption (hazard ratio, 2.36; 95% CI, 1.0-5.57; P = .05) and higher caloric intake (P = .04) were associated with risk of phenoconversion. CONCLUSIONS AND RELEVANCE: MeDi was not associated with phenoconversion; however, higher consumption of dairy products had a 2-fold increased risk and may be a surrogate for lower urate levels (associated with faster progression in manifest HD). Studies of diet and energy expenditure in premanifest HD may provide data for interventions to modify specific components of diet that may delay the onset of HD.
Keywords: Adult; Body Mass Index; Canada; Diet, Mediterranean; Disease Progression; Energy Intake; Female; Humans; Huntington Disease; Male; Medication Adherence; Middle Aged; Observation; Phenotype; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Questionnaires; Retrospective Studies; Severity of Illness Index; Time Factors; Trinucleotide Repeat Expansion; United States